Phase structure transformation and growth mechanism for iron oxide nanoparticles synthesized by mechanochemical method: A mini-review - Joseph Ekhebume Ogbezode; Nkechi Elizabeth Offia-Kalu; Abdulhakeem Bello; Vitalis Chioh Anye; Peter Azikiwe Onwalu (Journal of Alloys and Metallurgical Systems, 2024)
The various methods of synthesis of iron oxide nanoparticles (IONPs) have been extensively studied in several works of literature. These methods include physical, chemical, and biological nanosynthesis methods with applications in water filtration, environmental remediation, plant improvements, biomedicines, etc. These nanosynthesis approaches revolve around their mode of application, nanomaterial properties, and characterization mechanisms, while little effort has been made to investigate the effect of nanosynthesis parameters based on phase transformation and growth mechanisms of such IONPs. The parameters, which are physical, chemical, mechanical, mineralogical, and morphological, have proven to have tremendous implications on the magnetic behaviors, crystalline size, degree of crystallinity, lattice stain, and mechanical strength of the synthesized IONPs. Thus, this paper gives an overview of the effect of selected nanosynthesis parameters, potential mechanisms of the phase transformation, nanomaterial characterization, and growth mechanism of IONPs produced via the mechanochemical route. The study also suggests future perspectives on the need for further study on the reduction-oxidation process, reaction kinetics, and growth mechanism as influencing factors that can affect the phase structure transformation and alteration of magnetic properties of mechanochemically synthesized IONPs at various levels for suitability in nanotechnology advancement and applications in various fields.